2017
DOI: 10.1016/j.cyto.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37 suppresses the inflammatory response to protect cardiac function in old endotoxemic mice

Abstract: Myocardial inflammatory responses to endotoxemia are enhanced in old mice, which results in worse cardiac dysfunction. Anti-inflammatory cytokine interleukin (IL)-37 has a broad effect on innate immunoresponses. We hypothesized that IL-37 suppresses myocardial inflammatory responses to protect cardiac function during endotoxemia in old mice. Old (20–24 month) wild-type (WT), and IL-37 transgenic (IL-37tg) mice were treated with lipopolysaccharide (LPS, 0.5 mg/kg, iv) or normal saline (0.1 ml/mouse, iv). Six ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
(47 reference statements)
5
22
0
Order By: Relevance
“…Despite dampening the inflammatory state of the mice, hematopoietic IL-37 expression neither reduced the atherosclerotic lesion size nor the macrophage content of the lesions in the present study. This is in seeming contrast to other recent studies where treatment with recombinant IL-37 reduced atherosclerosis development in streptozotocin-induced diabetic apolipoprotein E-deficient ( Apoe −/− ) mice [ 25 ], and protected WT mice from endotoxemia-induced cardiac dysfunction [ 26 ] and damage-induced myocardial ischaemia/reperfusion injury via a reduction in inflammatory state [ 27 ]. Two reasons may account for the lack of effect of hematopoietic IL-37 on atherosclerosis development.…”
Section: Discussionmentioning
confidence: 56%
“…Despite dampening the inflammatory state of the mice, hematopoietic IL-37 expression neither reduced the atherosclerotic lesion size nor the macrophage content of the lesions in the present study. This is in seeming contrast to other recent studies where treatment with recombinant IL-37 reduced atherosclerosis development in streptozotocin-induced diabetic apolipoprotein E-deficient ( Apoe −/− ) mice [ 25 ], and protected WT mice from endotoxemia-induced cardiac dysfunction [ 26 ] and damage-induced myocardial ischaemia/reperfusion injury via a reduction in inflammatory state [ 27 ]. Two reasons may account for the lack of effect of hematopoietic IL-37 on atherosclerosis development.…”
Section: Discussionmentioning
confidence: 56%
“…Interleukin‐37 can protect transgenic mice against LPS treatment and stimulate the production of anti‐inflammatory cytokine IL‐10 as well as generating a greater resistance to infections, autoimmune diseases, and atherosclerosis (Li et al, ).…”
Section: Anti‐inflammatory Il‐37mentioning
confidence: 99%
“…Interleukin-37 can protect transgenic mice against LPS treatment and stimulate the production of anti-inflammatory cytokine IL-10 as well as generating a greater resistance to infections, autoimmune diseases, and atherosclerosis (Li et al, 2017). Activated MCs generate IL-1, IL-33, and TNF which are correlated with cartilage destruction in vivo and in vitro and could be inhibited by IL-37 (Siebert, Tsoukas, & Robertson, 2015).…”
Section: Anti-inflammatory Il-37mentioning
confidence: 99%
“…Expression of IL-37 suppresses LPS-induced MCP-1 and ICAM-1 production and NF-κB activation in cardiac microvascular endothelial cells (80). In addition, Xu et al found that IL-37 suppresses MPO expression and recombinant IL-37 effectively suppresses activation of the NF-κB signaling pathway, and finally results in an anti-inflammatory effect in AMI mice (77).…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%